The Relationship between Maternal Education, Household Spending Patterns, and Playtime in Secondary School Students’ Academic Achievement - Dewan, Krishna Pada; Islam, Md. Toriqul; Monir, Md. Moniruzzaman (Indonesian Journal of Social Research (IJSR), 2026)
Academic performance at the secondary level is a crucial determinant of students’ future educational attainment, employment opportunities, and socioeconomic mobility in developing countries. Despite improved access to secondary education in Bangladesh, significant disparities in academic achievement persist, largely driven by family socioeconomic conditions and students’ behavioral patterns. This study examines the influence of parental socioeconomic characteristics and students’ time-use behavior on secondary school academic performance using primary household-level data from Khulna district, Bangladesh. Data were collected through face-to-face surveys of 94 parents of students who passed the Secondary School Certificate (SSC) examination in 2023. Students’ academic performance is measured using SSC Grade Point Average (GPA), which is right-censored at the upper limit of 5; therefore, a Tobit regression model is employed to obtain unbiased estimates. The results show that maternal education, household income, educational expenditure, nuclear family structure, and study time have statistically significant positive effects on students’ GPA. In contrast, unstable paternal employment particularly day labor poor housing conditions, higher non-educational expenditure, and excessive time spent playing are negatively associated with academic performance. Empirically, each additional year of mothers’ schooling increases GPA by 0.071 points, while students whose fathers are engaged in day-labor employment score about 1.59 GPA points lower than those from farming households. Overall, the findings highlight the central roles of maternal human capital, household economic stability, family environment, and effective time management in shaping secondary-level academic outcomes. The study provides district-level evidence and supports policies aimed at promoting maternal education, assisting economically vulnerable households, improving home learning conditions, and encouraging balanced study habits to reduce educational inequality.